Modular Nanotransporters Deliver Anti-Keap1 Monobody into Mouse Hepatocytes, Thereby Inhibiting Production of Reactive Oxygen Species - Yuri V. Khramtsov; Alexey V. Ulasov; Andrey A. Rosenkranz; Tatiana A. Slastnikova; Tatiana N. Lupanova; Georgii P. Georgiev; Alexander S. Sobolev (MDPI AG, 2024)
Background/Objectives: The study of oxidative stress in cells and ways to prevent it attract increasing attention. Antioxidant defense of cells can be activated by releasing the transcription factor Nrf2 from a complex with Keap1, its inhibitor protein. The aim of the work was to study the effect of the modular nanotransporter (MNT) carrying an R1 anti-Keap1 monobody (MNTR1) on cell homeostasis. Methods: The murine hepatocyte AML12 cells were used for the study. The interaction of fluorescently labeled MNTR1 with Keap1 fused to hrGFP was studied using the Fluorescence-Lifetime Imaging Microscopy-Förster Resonance Energy Transfer (FLIM-FRET) technique on living AML12 cells transfected with the Keap1-hrGFP gene. The release of Nrf2 from the complex with Keap1 and its levels in the cytoplasm and nuclei of the AML12 cells were examined using a cellular thermal shift assay (CETSA) and confocal laser scanning microscopy, respectively. The effect of MNT on the formation of reactive oxygen species was studied by flow cytometry using 6-carboxy-2',7'-dichlorodihydrofluorescein diacetate. Results: MNTR1 is able to interact with Keap1 in the cytoplasm, leading to the release of Nrf2 from the complex with Keap1 and a rapid rise in Nrf2 levels both in the cytoplasm and nuclei, ultimately causing protection of cells from the action of hydrogen peroxide. The possibility of cleavage of the monobody in endosomes leads to an increase in the observed effects. Conclusions: These findings open up a new approach to specifically modulating the interaction of intracellular proteins, as demonstrated by the example of the Keap1-Nrf2 system.